Isolated segmental mega-diverticulosis of ileum: a rare presentation of acute intestinal obstruction - A., Veena; K. S., Hanumanthaiah; K., Manjunath; S., Sandeep; Kotera, Sai Suraj (International Surgery Journal, 2017)
We present an interesting case of acute intestinal obstruction where a woman, aged 26, presented to emergency room with constipation for 2 days and vomiting for 1 day. The examination and initial imaging suggested sub-acute intestinal obstruction, since the condition progressed she was taken to operating room for laparotomy. The intra-operative findings revealed isolated segmental mega-diverticulosis of ileum. She underwent resection of terminal ileum and caecum with ileo-colic anastomosis. Pathological evaluation of specimen showed diverticular features. Ileal diverticulosis excluding Meckel’s is an extremely rare entity and complicating into acute intestinal obstruction is strange. With a low prevalence and absence of suspicion for it, diagnosis will be made intra operatively most of the time.